The Defense Mechanisms and Dynamics of Self-Defense of the Characters in the Film ‘Semusim Setelah Kemarau’ and the Lesson Plan: - Fadilah, Nur; Rosidah, Ilmiyatur; Sugianti (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
This study aims to describe the personality structure and defense mechanisms of the characters in the film Semusim Setelah Kemarau by Dyan Sunu Prastowo using a literary psychology approach based on Sigmund Freud's psychoanalytic theory. This theory highlights the interaction between the id, ego, and superego in shaping individual behavior and the role of self-defense mechanisms in dealing with mental stress. This study uses a qualitative descriptive method with data collection techniques through observation of scenes, dialogues, and expressions of the characters in the film. The results show that each of the main characters, Kaldera, Papa Kaldera, Handaru, and Mama Kaldera, has a different personality structure and displays complex psychological dynamics. The most dominant forms of self-defense mechanisms include repression, rationalization, projection, regression, and sublimation. Kaldera, as the central character, shows intense inner conflict due to childhood trauma and a strained relationship with his father. In addition, the results of this study are implemented in the lesson plan (RPP) for Indonesian Language subjects, specifically in the material analyzing characters, plots, and conflicts in narrative texts or films. The lesson plan (RPP) that was prepared emphasized film-based learning activities that train students to analyze the character's personality structure, identify self-defense mechanisms, and understand internal conflicts in the story. The learning implementation plan for the defense mechanisms and dynamics of the characters in the film Semusim Setelah Kemarau by Dyan Sunu Prastowo uses the constructivist approach of Needham's five-phase model through a Google form containing four initial activities, 15 core activities, and two final activities.